From Continuity to Rhythm II : Adjustment and Entrainment - Miranda Medina, Juan Felipe (2022)
This work is the second part of the article “From Continuity to Rhythm” (Acta Se-miotica, II, 3, 2022), where I set out to define rhythm as a semiotic concept. The cornerstones for such a definition are Victoria Santa Cruz’s concept of Rhythm as an active and continu-ous principle of integration, Landowski’s understanding of continuity, Leibniz’s notion of Harmony, the physical concept of entrainment, and the formal definition of feedback from engineering as a framework to understand manipulation, adjustment and entrainment. The main contributions are: 1) analysing the regimes of adjustment and manipulation in terms of feedback, 2) establishing a link between manipulation and adjustment, showing that the former is a simplification of the latter, 3) providing a semiotic definition of entrainment that considers five different dimensions, expressing manipulation and adjustment as specific modes of entrainment, 4) providing a semiotic definition of Rhythm as a dynamic unification process departing from Leibniz’s notion of Harmony, 5) questioning Leibniz’s Harmony in favor of an active view of Rhythm that not only produces order or common properties, but that actively strives to maintain them in virtue of feedback.